1998
DOI: 10.1002/ana.410430108
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion‐weighted imaging defects during spontaneous migrainous aura

Abstract: Perfusion- and diffusion-weighted magnetic resonance imaging was performed during spontaneous visual auras in four migraineurs. Alterations in relative cerebral blood flow (16-53% decrease), cerebral blood volume (6-33% decrease), and tissue mean transit time (10-54% increase) were observed in the gray matter of occipital cortex contralateral to the affected visual hemifield. No changes in the apparent diffusion coefficient were observed either while the patients were symptomatic or after resolution of the vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
217
0
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 328 publications
(228 citation statements)
references
References 21 publications
7
217
0
4
Order By: Relevance
“…Our data confirmed previous reports that CSD-like phenomena can be seen with neuroimaging techniques (7,10,12,15,19,20,28). Like those previous studies, our data indicated a slowly spreading area of abnormal blood flow in the occipital lobe during migraine aura.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data confirmed previous reports that CSD-like phenomena can be seen with neuroimaging techniques (7,10,12,15,19,20,28). Like those previous studies, our data indicated a slowly spreading area of abnormal blood flow in the occipital lobe during migraine aura.…”
Section: Discussionsupporting
confidence: 92%
“…These include planar Xenon (6)(7)(8)(9), single photon emission tomography (8,(10)(11)(12)(13)(14), positron-emission tomography (15,16), magnetoencephalography (17,18), and MRI (19)(20)(21). Each demonstrated one or more aspects of CSD associated with migraine aura.…”
mentioning
confidence: 99%
“…High-field strength functional MRI to map progression of the BOLD events during migraine aura confirmed previous reports that CSD-like phenomena can be seen with neuroimaging techniques [80]. A slowly spreading area of perturbed BOLD signal has also been described in the occipital lobe during migraine aura.…”
Section: The Migraine Aura: Ascending To the Central Origin Of Migrainesupporting
confidence: 82%
“…CSD is a wave of neuronal and glial depolarisation, followed by long-lasting suppression of neural activity, and it can be evoked in mammals with lissencephalic [63,64] or folded cortex [65]. Human neuroimaging such as planar Xenon [66][67][68][69], single photon emission tomography [68,[70][71][72][73][74] positron-emission tomography [75,76], magnetoencephalography [77,78] and MRI [79][80][81] support the hypothesis that CSD underlies migraine [82]. However many subjects never experience symptoms of typical visual auras in studies showing spreading hypoperfusion [75] or blood oxygenation level-dependent (BOLD) signal changes [79], and the initial hyperaemia characteristics of CSD were not directly demonstrated in human cortex.…”
Section: The Migraine Aura: Ascending To the Central Origin Of Migrainementioning
confidence: 99%
“…All such ionic unbalance is believed to depolarize adjacent neurons and glia, thereby facilitating its spread. An advancing wave of brief excitation would then be followed by a longerlasting inhibition of spontaneous and evoked neuronal activity that traverses the cortex (Somjen 2001, Goadsby 2007, Lauritzen 1994, Cutrer et al 1998, Hadjikhani et al 2001and Bowyer et al 2001. In humans, evidence for a causal role of CSD in the aura comes from functional magnetic resonance imaging (fMRI) performed during migraine attacks with aura (Hadjikhani et al 2001) The nature and mechanisms of the primary brain dysfunction leading to the activation of the meningeal trigeminal nociceptors remain incompletely understood (for reviews see Charles 2009, Goadsby et al 2009a, Levy et al 2009 and it is controversial whether CSD can initiate the migraine headache cascade by itself.…”
Section: Migraine and Familial Hemiplegic Migraine (Fhm)mentioning
confidence: 99%